Microsized and nanosized carriers for nonsteroidal anti-inflammatory drugs formulation challenges and potential benefits - Čalija, Bojan (Academic Press, an imprint of Elsevier, 2017)
Microsized and Nanosized Carriers for Nonsteroidal Anti-Inflammatory Drugs: Formulation Challenges and Potential Benefits provides a unique and complete overview of novel formulation strategies for improvement of the delivery of NSAIDs via encapsulation in microsized and nanosized carriers composed of different materials of natural and synthetic origin. This book presents the latest research on advances and limitations of both microsized and nanosized drug carriers and NSAIDs before discussing the formulation aspects of these drug carriers that are intended for oral, dermal, and transdermal administration of NSAIDs. In addition, functionality of these materials as potential excipients for microsized and nanosized carriers is discussed and debated. Practical solutions for improving effectiveness of these drugs are included throughout the book, making this an important resource for graduate students, professors, and researchers in the pharmaceutical sciences.Covers a wide range of microsized and nanosized carriers in one resource, including particulate carriers (microparticles, nanoparticles, and zeolites) and the soft colloidal carriers, such as micro-emulsions and nano-emulsionsPresents the reader with various formulation approaches dependent on the characteristics of the material, model drug, and desired route of administration Approaches are based on the latest research in the area and formulation strategies may have broader applications to the encapsulation of other active pharmaceutical ingredients